Pyocolecyst in Elderly Patients with Jejunoileal Diverticulosis as a Transoperative Finding. Clinical Case - Falcón-Cancino, Luis Arturo; Flores-López, Alejandro Alberto; Ferrera-Salas, Rilma Carmen; García-Flores, Rubén; Carrillo-Pinto, Laura Daniela Caridad; Cruz-Méndez, Adriana Teresa; Padrón-Arredondo, Guillermo; Villalobos-Rodríguez, Alejandro Lenin (British Journal of Healthcare and Medical Research, 2023)
Introduction: Small intestine diverticulosis is a rare finding, recognized as a cause of non-specific symptoms of the gastrointestinal tract, and however, it is capable of causing life-threatening complications. It frequently occurs in older individuals, as was our case. An incidence between 0.2 to 4.5% is in autopsies reported. Small intestinal diverticula contain only mucosal and submucosal layers, which herniated through the muscular layer and pseudodiverticula classified. Clinical Case: A 95-year-old female with a history of hospitalization one year ago due to cholangitis associated with choledocholithiasis, which ERCP resolved, was discharged for not accepting elective cholecystectomy. She started with epigastric pain 48 hours before hospitalization, accompanied by nausea and vomiting on one occasion of gastro biliary content. Upon questioning, she reported abdominal pain in the right colic frame, present uresis, and no bowel movements. Integrated diagnosis of acute cholecystitis, emergency open cholecystectomy is determined and was done complete cholecystectomy was, later as a finding multiple thin-walled and vascularized diverticula were observed located in the jejunum 70 cm from the angle of Treitz and running towards the ileum, without apparent intestinal distress or perforation, thus concluding the surgical procedure. Discussion: Gallstone disease is a common health problem with an annual incidence of 1 to 4% in the general Western population. For uncomplicated jejunal diverticulosis, the treatment depends on the clinical stadium presentation and its complications, hence the importance of imaging techniques in pre-surgical diagnosis. In uncomplicated jejunal diverticulosis, the treatment is unnecessary; in uncomplicated jejunal diverticulitis, treatment is conservative, with only antibiotics; in perforated diverticulitis, intravenous antibiotic therapy and can be chosen CT-guided drainage and open or laparoscopic surgery is the choice in the case of peritonitis.